Assessment of workplace hazards among working children in al amen city, Baghdad - Sahb Al Saidi, Ali Abd Ali (AL-Kindy College Medical Journal, 2010)
Back ground: One out of six children in theworld today is involved in child labor, doingwork that is damaging to his or her mental,physical and emotional development.Objective: Assessment of some healthproblems among the studied working children.Method; A cross-sectional study wasconducted in Al Amen Primary Health Care(PHCC) during the period from January toAugust 2009, a sample of 6048 children wereselected randomly(3218girls and2866 boys agebetween 5-17 years ) and interviewed to collectinformation using a structured questionnaireform, information related to different aspectsof child labor prevention were included in theform as well as a general medical examinationand laboratory assessment.Results:. The frequency of child labor was10.95% among the children study, and thedetection of work related illnesses amongworking children was observed in 402 workingchildren(60.36%).While work related accidentswas 264(39.63%).Both sexes showeddifference in frequency of labor (77% boysand 23% girls).there was associationbetween malnutrition and child labor(x2=64.11,df=1,p-value